Стародавнє населення Прикарпаття і Волині (доба первіснообщинного ладу) - Кучінко, М.М. (Археологія, 1977)
Рецензія на книгу: Стародавнє населення Прикарпаття і Волині (доба первіснообщинного ладу), вид-во «Наукова думка». К., 1974 р., 286 с.